SAT0533 Polvas – retrospective registry of polish patients with anca-associated vasculitides. (12th June 2018) - Wójcik, K.; Kur-Zalewska, J.; Masiak, A.; Dębska-Ślizień, A.; Jeleniewicz, J.; Jakuszko, K.; Głuszko, P.; Wisłowska, M.; Brzosko, I.; Hawrot-Kawecka, A.; Musiał, J.
Abstract : Background: Vascultides are a heterogeneous group of rare diseases with unknown etiology and the clinical spectrum ranging from life–threatening systemic disease to minor isolated skin changes. Present nomenclature and definitions of systemic vasculitides have been proposed in 2012 at the International Chapel Hill Consensus Conference. 1 Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) belong to the small to medium-size vessel systemic diseases comprising granulomatosis with polyangitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA). Objectives: We decided to retrospectively analyse a large cohort of Polish AAV patients coming from referral centres – members of the Scientific Consortium of the Polish Vasculitis Registry (POLVAS). 2, 3 Methods: We conducted a systematic multicenter retrospective study of adult patients diagnosed with AAV between Jan 1990 and Dec 2016 Patients were enrolled to the study by 9 referral centres (14 clinical wards: – rheumatology – 10, nephrology – 2, metabolic diseases – 1, clinical immunology −1) from 7 Voivodships populated by 22, 3 mln inhabitants (58, 2% of the Polish population). Patient data have been collected according to the uniform protocol in the POLVAS registry. Results: Distribution of AAV in the Polish population resembles that of north European cohorts. 4 In POLVAS registry 417 (66.7%) patients were diagnosed with GPA, 106 (17.0%) with MPA and 102 (16, 3%) with EGPA. Male-to-female ratios were almost 1:1 for GPA (210/207) and MPA (54/52), but EGPA wasd twice more frequent among women (34/68). Clinical manifestations and organ involvement were analysed both by clinical phenotype (GPA, MPA, EGPA) and ANCA specificity (anti-PR3+, and anti-MPO+)Analysis by ANCA specificity showed no apparent difference as compared to phenotype analysis. Clinical manifestations of different AAV in the polish population seems very similar to other European countries. Conclusions: This is the first multicenter retrospective study of the Polish patients sufferng from with AAV. Demographic characteristics and disease manifestations of AAV patients in POLVAS registry follow the same pattern as those from other European countries. 4 References: [1] Jennette JC, et al. Arthritis Rheum2013Jan;65(1):1–11. [2] Padjas A, et al. Pol Arch Med Wewn2014;124(3):143–4. [3] Musia&x0142; J, Wójcik K. Pol Arch Intern Med2017Jan 31;127(1):71–72. [4] Bajema, et al. Kidney Int Rep2017;1018–1031. Disclosure of Interest: None declared